Réponses

2014-03-21T14:23:19+01:00
Pour x=3 A= 2*3 au cube - 7*3 au carre +6 A=54-69 A=-15 pour x=-5 A= 2*(-5) au cube - 7*(-5)au carre +6 A= -250 - 781 A= -1031
Meilleure réponse !
2014-03-21T14:27:10+01:00
pour x=3 :

A= 2x3x3x3-7x3x3+6
A= 6x3x3-21x3+6
A= 18x3-63+6
A= 54-63+6
A= (-9)+6
A= (-3)


Pour x=5 :

A= 2x5x5x5-7x5x5+6
A= 10x5x5-35x5+6
A= 50x5-175+6
A= 250-175+6
A= 75+6
A= 81
pour x=3 :

A= 2x3x3x3-7x3x3+6
A= 6x3x3-21x3+6
A= 18x3-63+6
A= 54-63+6
A= (-9)+6
A= (-3)

Pour x=5 :

A= 2x5x5x5-7x5x5+6
A= 10x5x5-35x5+6
A= 50x5-175+6
A= 250-175+6
A= 75+6
A= 81